Preliminary Research on Artificial Intelligence-Based Learning Video Media in Economics Subject in High School - M Topit Hidayat; Armiati Armiati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: Addressing this gap requires preliminary research on the development of AI-based educational videos. This research focuses on high school economics subjects and aims to examine how such media can help improve students' understanding of complex economics material. Method: This research employs the ADDIE development model; however, at this stage, the study is only at the preliminary phase, specifically the needs analysis. This phase involves an analysis of the needs of prospective users (students and teachers), curriculum analysis, and an analysis of student characteristics. The methods employed include interviews, documentation studies, and surveys of students to identify preferences and challenges faced in the economics learning process. Results: The findings indicate that some teachers tend to use conventional learning media that are less effective in enhancing students' understanding of economic concepts.Furthermore, there is a clear need for innovative learning media that can facilitate students' comprehension of economic concepts more effectively. Based on these findings, it can be concluded that AI-based learning media represents a relevant solution to address the challenges of learning in the digital era, particularly in improving the quality of economics education at the high school level. Novelty: conducting a comprehensive preliminary needs analysis as the basis for developing AI-based educational videos for high school economics learning. The integration of curriculum analysis, teacher and student needs, and student characteristics provides a systematic foundation for designing AI-supported learning media that is pedagogically relevant and responsive to the demands of digital-era education.